ROLA KRYTYKI W KSZTAŁTOWANIU WIZERUNKU CZŁOWIEKA W INTERAKCJACH MIĘDZYOSOBOWYCH - Kaus, Jerzy (Scripta Neophilologica Posnaniensia, 2019)
The article aims at analyzing the role of criticism in forming the image of human being in interpersonal interactions. The discussion starts with defining criticism and image. In order to define the concept of criticism, the definition proposed by Mirosław Karwat (2007) is applied. Next, the notion of image is analyzed by means of Stanisław Puppel’s (2016) definition. Finally, the role of criticism in forming the image of human being is scrutinized by means of a survey which was carried out among 20 students studying in Poznań. The results are discussed in the final part of the article.